Role of dermatoglyphic features associated with periodontal diseases - Surekha Rathod; Shweta Maske; Abhay Kolte; Ishita Wanikar (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim of this study is to correlate the features of palmer dermatoglyphic with aggressive, chronic periodontitis, and periodontally healthy controls. Materials and Methods: A total of 45 patients with mean age of 18-45 years were equally divided into three groups comprising 15 patients in each group as follows: Group I-periodontally healthy, Group II-aggressive periodontitis, and Group III-chronic periodontitis. The fingertip patterns of all the patients in each group were obtained and analyzed with the help of magnifying glass. The collected data were subjected to statistical analysis. Results: An increased frequency of whorls was found in patients with aggressive periodontitis and chronic periodontitis, whereas increase frequency of ulnar loop was found higher in the healthy group. Conclusion: Within the limitations of the study, it was found that whorl patterns were in greater frequency in aggressive periodontitis patients. However, further studies with larger sample size are required to arrive at a conclusive report to correlate dermatoglyphic patterns in patients.